A study of the foil explosion in vacuum using spectral streak camera diagnostics; Physics of Plasmas; Vol. 28, iss. 6 - Baksht R. B. Rina Borisovna; Tkachenko S. I.; Zhigalin A. S. Aleksandr Sergeevich; Russkikh A. G. Aleksandr Gennadievich; Oreshkin V. I. Vladimir Ivanovich (2021, 2021)
Title screen